Keterikatan Kerja sebagai prediktor Eudaimonic Well-Being Pada Pegawai - kadek putri lestari wardani; Ni Putu Lilik Agestin (Psikodinamika: Jurnal Literasi Psikologi, 2026)
The rapid development of Society 5.0 places human resources as the central driver of organizational success, making employee well-being an important aspect to consider. This study aims to examine the relationship between work engagement and eudaimonic well-being among employees. The research used a quantitative survey design involving 135 permanent employees from a company in the airport service sector. Data were collected using self-report questionnaires measuring work engagement and eudaimonic well-being. The instruments used were adapted from established scales, and data were analyzed using correlation analysis. The results showed that work engagement has a positive relationship with eudaimonic well-being. Employees who demonstrate higher levels of vigor, dedication, and absorption in their work tend to experience greater meaning in life, personal growth, and eudaimonic well-being. These findings highlight the importance of fostering work engagement as a strategy to enhance wellbeing in the workplace Keywords: eudaimonic well-being; employees; work engagement; workplace